Doxorubicin delivery by pYEEIE peptide-functionalized rhodiola rosea-derived exosome-like nanovesicles for targeted melanoma therapy - Duan, Meitao; Chen, Binbin; Yi, Xue; Mahal, Ahmed; Song, Linwei; Xu, Moxun; Obaidullah, Ahmad J.; Yu, Shuwei; Wang, Chen (Frontiers in Pharmacology, 2025)
IntroductionMelanoma is the most common cause of skin cancer-related deaths due to its aggressive nature. Plant-derived exosome-like nanovesicles (PELNs) are promising natural nanoparticles for therapeutic applications owing to their biocompatibility and diverse bioactive components. However, research on Rhodiola rosea-derived exosome-like nanovesicles (RELNs) remains limited.MethodsThis study evaluated the therapeutic efficacy and safety of a novel targeted drug delivery system, pYEEIE peptide-functionalized RELNs loaded with doxorubicin (DOX) (pYEEIE-RELNs-DOX), in melanoma-bearing mice.ResultsFluorescence imaging and histopathological assessments demonstrated that pYEEIE-RELNs-DOX exhibited superior tumor-targeting ability and significantly inhibited melanoma growth compared to free DOX and non-targeted RELNs-DOX. Importantly, pYEEIE-RELNs-DOX showed no toxicity to major organs (heart, liver, spleen, lungs, and kidneys), whereas free DOX induced cardiac tissue damage. Meanwhile, the serum ALT and AST levels remained normal, indicating no liver cell damage.ConclusionThese findings highlight the potential of pYEEIE-RELNs-DOX as a low-toxicity, high-efficacy targeted delivery system for melanoma therapy, providing a foundation for clinical translation.